MXD/MIZ1 transcription regulatory complexes activate the expression of MYC‐repressed genes. Issue 12 (12th May 2021) - Shostak, Anton; Schermann, Géza; Diernfellner, Axel; Brunner, Michael
Abstract : MXDs are transcription repressors that antagonize MYC‐mediated gene activation. MYC, when associated with MIZ1, acts also as a repressor of a subset of genes, including p15 and p21 . A role for MXDs in regulation of MYC‐repressed genes is not known. We report that MXDs activate transcription of p15 and p21 in U2OS cells. This activation required DNA binding by MXDs and their interaction with MIZ1. MXD mutants deficient in MIZ1 binding interacted with the MYC‐binding partner MAX and were active as repressors of MYC‐activated genes but failed to activate MYC‐repressed genes. Mutant MXDs with reduced DNA‐binding affinity interacted with MAX and MIZ1 but neither repressed nor activated transcription. Our data show that MXDs and MYC have a reciprocally antagonistic potential to regulate transcription of target genes. Abstract :